(untitled) (World Economics and Finance Bulletin, 2024)
This study aimed to identify the impact of functional alienation on organizational citizenship behaviors, by focusing on the dimensions of functional alienation (loss of purpose, self-alienation, non-informativeness, weak relationship with others) and then determine the relationship of alienation with the behavior of organizational citizenship, which was represented by four sub-dimensions, namely (voluntary participation, altruism, civility, awakening of conscience), and the middle management was selected at the University of Samarra represented by the heads of scientific departments In which as a sample of the study, and the number of (31), and the number of forms recovered and valid for statistical analysis (26) form, and the researcher used the questionnaire after a major tool to collect data and information, has been used program (SPSS V.24) to analyze the data was based on the simple linear regression test and correlation coefficient, and the results of the study showed that the sample surveyed have mThere is a low level of functional alienation and that there is a goal and standard for the heads of departments in the performance of their administrative work and they have the ability to influence others, and this is confirmed by the results of the description and diagnosis through the decrease in the arithmetic mean from the hypothetical mean for all dimensions of functional alienation, and it also turned out that they have a good level of organizational citizenship behaviors and a positive and moral correlation between job alienation and citizenship behaviors Organizational and at the macro level of dimensions and sub-level, and this means that the dimensions of functional alienation that have been adopted affect the decrease in citizenship behavior, and in the light of the conclusions a set of recommendations have been developed, namely the need to increase interest in participation and expand the base of freedom in the expression of ideas for work and encourage innovation while taking the views of department heads and workers with them in fateful decisions and encouraging the effortEfforts to provide the opportunity for senior management to reduce the manifestations of alienation, while increasing the ability of department heads to rely on themselves in some decisions and administrative work and reduce reference